ChemInform Abstract: Organocatalyzed Asymmetric Oxidative Coupling of α‐Csp3—H of Tertiary Amines to α, β‐Unsaturated γ‐Butyrolactam: Synthesis of MBH‐Type Products. Issue 14 (April 2015) - Ma, Yunxia; Zhang, Gen; Zhang, Jinlong; Yang, Dongxu; Wang, Rui
Abstract: For the first time the organocatalytic type of the title reaction catalyzed by a bifunctional thiourea catalyst is presented.